Trinexapac-ethyl application doses and times on productive performance of white oat cultivars - Henrique dos Santos Fernandes, Carlos; Márcio Antunes Arruda, Klever; Cristina de Batista Fonseca, Inês; Sawada Buratto, Juliana; Zucareli, Claudemir (Revista Ciência Agronômica, 2024)
This study aimed to assess the effect of different doses and times of application of the growth regulator trinexapac-ethyl on the productive performance of white oat cultivars. The experiment was carried out in Londrina, Paraná State, Brazil, in the 2019 and 2020 seasons using the white oat cultivars IPR Artemis and URS Corona. The experimental design was a randomized block with four replications arranged in a 4 × 3 factorial scheme, conducted separately for each cultivar, with four doses of trinexapac-ethyl (0, 50, 100, and 150 g ha−1) and three times of application (T1, first node noticeable; T2, first node visible and second node noticeable; and T3, second node visible and third node noticeable). The following agronomic characters were evaluated: plant height, panicle length, panicles per square meter, spikelets per panicle, grains per spikelet, grains per panicle, thousand grain weight,lodging percentage, and grain yield. Application of trinexapac-ethyl at doses of 100 or 150 g ha−1 at T2 or T3 reduced panicle length, spikelets per panicle, and grains per panicle in IPR Artemis and URS Corona. However, it also reduced plant height and increased panicles per square meter and yield in both cultivars. These same doses and times of application resulted in a significant reduction in lodging.